Escape from Sobibor [videorecording (DVD)] - Arkin, Alan; Pacula, Joanna, 1957-; Hauer, Rutger, 1944-2019-; Smith, Howard K. (Howard Kingsbury), 1914-2002; Rashke, Richard L. (Echo Bridge Home Entertainment, 2013)
The true story of a partially successful mass escape from a WWII Nazi extermination camp in Poland.